Characterization of traditional production systems of sugarcane for panela and some prospects for improving their sustainability (2017)
Sugarcane used for the production of “panela” (unrefined cane sugar) is a crop of great importance for Colombia’s rural economy. Additionally, it serves a fundamental role in the food security and sovereignty of the Colombian population and daily consumption. However, the small production system presents problems of sustainability, as a direct consequence of its technological arrears and loss of interest in this crop. In this study, a characterization of 30 small productive units located in three municipalities in Antioquia was performed with the objective of identifying the problems associated with this production system and stablish the causes associated with loss of area dedicated to this crop in the study area. The results demonstrate that in the region of study, this production system and its associated agro-industry have problems associated with low technological level, poor infrastructure, deficient agro-industry processing and low levels of associativity and marketing. This situation has generated a low economic solvency for the farmers, leading many to abandon this activity and migrate towards other economic sectors. The findings of this study indicate the need to reengineer this production system, for which they could make technological adaptations that improve productivity and product quality and generate added value. On the other hand, must the rural countryside attractive to avoid the loss of labor and make young people become interested in this economic activity. As strategies to improve productivity, we suggest the effective use of information technologies, improve rural living conditions, increase associativity and value added, involve the consumer in the production chain and design development policies for the entire chain of value.